2020
DOI: 10.21203/rs.3.rs-40800/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Food from the Campus: Understanding Africa’s Transition to Sustainable Urban FoodSecurity during the Covid-19 Pandemic

Abstract: This paper takes a critical look at the 20-hectares research/demonstration farm at Bayero University Kano’s Centre for Dryland Agriculture (CDA) in Kano, Nigeria. The paper examines how knowledge-based mode farm driven by scientific, ethical, and technological innovations contributes to ensuring some level of food security during the COVID-19 pandemic. The main research question driving the current study is: in what ways can universities demonstration farms support urban food security during pandemics? The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A study conducted by the Bayero University Kano’s Centre for Dryland Agriculture in Nigeria found that 75% of the women interviewed reported that no discrimination was placed on them by farm operators when attending markets [ 24 ]. However, these statistics must be interpreted carefully, as only 7/26 of those interviewed were women.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted by the Bayero University Kano’s Centre for Dryland Agriculture in Nigeria found that 75% of the women interviewed reported that no discrimination was placed on them by farm operators when attending markets [ 24 ]. However, these statistics must be interpreted carefully, as only 7/26 of those interviewed were women.…”
Section: Resultsmentioning
confidence: 99%
“…In general, for both crises, the first affected factor was felt through a decline in crop production due to the reduction in the labour force and workforce mobility (e.g., for Ebola [34,35]; for COVID-19 [36]). This is exacerbated for women and girls facing a higher burden of childcare and household responsibilities since the pandemic (Zambia, Kenya and Ghana [37], and Nigeria [38]). According to Kodish et al, women also tend to fall ill more frequently [34], as their social role in family healthcare makes them particularly exposed to potential contamination [6], thereby affecting their capacity to work.…”
Section: Impact Of Pandemics On Each Of the Four Pillars Of Food Securitymentioning
confidence: 99%